Comparing the Effectivity of Intravenous Analgetic Tramadol and Intravenous Paracetamol for Acute Post-Percutaneous Nephrolithotomy - Leonard Khriestsandi Saleh; Alvarino Alvarino; Peri Eriad Yunir (Indonesian Journal of Multidisciplinary Science, 2023)
There are many management strategies and interventions both preoperative, intraoperative, and postoperative  that can be carried out in dealing with postoperative pain. Guidelines for pain management have been prepared  by the American Pain Society (APS) with recommendations from  the American Society of Anesthesiologists (ASA) where there are many recommendations in postoperative pain management in adults or children by promoting the provision of preoperative education, the use of various modalities both pharmacological and non-pharmacological to the establishment of pain management procedures or policies in each institution. For this reason, the author was interested in examining the comparison of the effectiveness of analgesia between intravenous tramadol and intravenous Paracetamol in minimally invasive Percutaneous Nephrolithotomy (PCNL) postoperative patients at RSUP Dr. M. Djamil Padang. The research was a prospective study with a single-blind randomised controlled trial design. The data used were sourced from clinical trials conducted on post-PCNL patients divided into two subgroups given intravenous tramadol analgetics and others given Paracetamol tablets. In this study, the incidence of Nephrolithiasis was obtained, which was dominated by the male sex, compared to women and suffered a lot at the age of 41-60 years. There was a significant difference in VAS effectiveness between the use of Paracetamol IV and Tramadol IV in post-PCNL patients. The use of Paracetamol may be considered to replace tramadol in the disappearance of acute pain after PCNL postoperative patients in those patients who are allergic to tramadol.